Evolution of Boron Nitride Structure upon Heating - Hang, Nguyen Thi Thuy (Communications in Physics, 2017)
The evolution of structure upon heating of hexagonal boron nitride nanoribbon (h-BNNR) model is studied via molecular dynamics simulation. The temperature is increased from 50K to 5500K in order to observe the change of the structure during heating process. Various thermodynamic quantities related to the change of structure are calculated such as radial distribution functions, Lindemann criterion, the occurrence/growth of liquidlike atoms, the formation of clusters, and ring statistics. The melting point is defined. The phase transition from solid to liquid states exhibits first order behavior.